PEMBELAJARAN DI ERA DIGITAL - Arisanti, Nani; Qolbiyah, Aini; Zulhendri, Zulhendri (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this study is to determine learning in the digital era. The approach in this writing uses a quantitative descriptive method. The study involved 100 grade 10 students at SMK Negeri 5 Pekanbaru. The results showed that the use of internet access: 24% of students use cellphones for YouTube, 45% for games, 14% for TikTok, 10% for Instagram and only 7% use them for studying. 2) Digital learning: 39% of students like Google Classroom, 23% via WhatsApp, 15% via Zoom, 16% via Telegram and 7% via Edmodo. The way of learning in integrating the use of technology that enables appropriate learning for students "Blended learning allows for reflection on learning